Cost‐effectiveness of risk‐based breast cancer screening: A systematic review. Issue 4 (1st May 2021) - Khan, Shah Alam; Hernandez‐Villafuerte, Karla Vanessa; Muchadeyi, Muchandifunga Trust; Schlander, Michael
Abstract: To analyse published evidence on the economic evaluation of risk‐based screening (RBS), a full systematic literature review was conducted. After a quality appraisal, we compared the cost‐effectiveness of risk‐based strategies (low‐risk, medium‐risk and high‐risk) with no screening and age‐based screening. Studies were also analysed for modelling, risk stratification methods, input parameters, data sources and harms and benefits. The 10 modelling papers analysed were based on screening performance of film‐based mammography (FBM) (three); digital mammography (DM) and FBM (two); DM alone (three); DM, ultrasound (US) and magnetic resonance imaging (one) and DM and US (one). Seven studies did not include the cost of risk‐stratification, and one did not consider the cost of diagnosis. Disutility was incorporated in only six studies (one for screening and five for diagnosis). None of the studies reported disutility of risk‐stratification (being considered as high‐risk). Risk‐stratification methods varied from only breast density (BD) to the combination of familial risk, genetic susceptibility, lifestyle, previous biopsies, Jewish ancestry and reproductive history. Less or no screening in low‐risk women and more frequent mammography screening in high‐risk women was more cost‐effective compared to no screening and age‐based screening. High‐risk women screened annually yielded a higher mortality rate reduction and more quality‐adjusted life years at the expense of higher cost and false positives. RBS can be cost effective compared to the alternatives. However, heterogeneity among risk‐stratification methods, input parameters, and weaknesses in the methodologies hinder the derivation of robust conclusions. Therefore, further studies are warranted to assess newer technologies and innovative risk‐stratification methods. Abstract : What's new? Most countries have set up population‐based mammography screening programmes based on women's age. However, the potential psychosocial harms, over‐diagnosis, and increased costs together with the growing understanding of breast cancer risk factors have led researchers to seek alternative screening paradigms. This full systematic literature review compares the cost effectiveness of risk‐based screening with no screening and age‐based screening in the general population. The findings suggest that risk‐based screening can be an economically efficient alternative and could potentially substitute current breast cancer screening programmes. Moreover, the review identifies several limitations that negatively impact the studies' methodological robustness and proposes possible solutions.